A Legal Study of Patients with Mental Health Disorders Due to Misdirected Love - Novia Maharani, Fitri; Eka Pratama, Risky; Rina Susanti, Destina; Nazera Arfananda, Zaky (Ethos and Pragmatic Law Review, 2025)
The phenomenon of mental health disorders arising from misguided love has become an increasingly relevant social issue amidst increasing emotional stress in interpersonal relationships. This journal examines the legal position of patients with mental health disorders caused by unhealthy romantic relationships, such as obsessive, manipulative, or emotionally abusive love. This study aims to examine legal protection for individuals who experience mental disorders due to detrimental love dynamics, as well as to analyze the relationship between psychological aspects and the legal responsibilities of the parties involved. The approach method used is normative legal with a literature study of laws and regulations, jurisprudence, and relevant literature. The results of the study show that although legal protection for people with mental disorders has been regulated in the Mental Health Law and the Criminal Code, there are no specific regulations governing the legal consequences of romantic relationships that cause mental disorders. Therefore, it is necessary to formulate a legal policy that is more responsive to forms of emotional violence in romantic relationships in order to guarantee the rights and recovery of victims as a whole.